Identifying the role of the sending state in the emigration of health professionals: a review of the empirical literature. (4th May 2017) - Cabanda, Exequiel
Abstract : There is a growing research interest in how sending states manage the emigration of health professionals. While the 'push' and 'pull' factors depict sending states as passive actors in this process, emergent studies are revealing them to be active actors with an articulated policy agenda. Using a variety of examples from the empirical literature, this paper identifies the multiple roles that sending states play in the emigration of doctors and nurses. The current findings contribute to the international migration literature in three ways. Firstly, this paper emphasizes that sending states are active actors in the health professional migration. Secondly, it shows that sending states adopt one of the three strategies: (1) introduce restrictive measures to delay the mobility of health professionals; (2) respond to market demands by producing and promoting emigration; and (3) implement a combination of these two strategies. Lastly, this paper highlights how sending states institutionalize gendered emigration through a bilateral cooperation in nurse migration. Missing from the extant literature are studies on competing beliefs, motivations, and technical information informing the strategies of sending states. This paper concludes by presenting a research agenda to further examine how and why sending states are active actors in the health professional migration.